2016
DOI: 10.1007/s10973-016-5461-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional effects on differences of coal char reactivity between air and oxy-fuel combustion in thermogravimetric experiments

Abstract: Oxy-fuel combustion can realize large-scale CO 2 capture and low NO x emission from coal-fired power plants, while the evaluation of coal reactivity differences between air and oxy-fuel conditions is of importance for retrofitting existing conventional boilers to oxy-fuel ones. Here, two sets of specially designed experiments were contrastively conducted to assess the diffusional limitation effects on differences of coal char reactivity between air (O 2 /N 2 ) and oxy-fuel (O 2 /CO 2 ) combustion in nonisother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In TGA, the solid sample is in a packed state on the crucible, and the gas has to diffuse from the gas cylinder to the TGA crucible. It is commonly acknowledged that the mass transfer limitations occurring inside the TGA will underestimate the kinetics. The mass transfer limitation can be improved by decreasing the mass of the solid amine sorbent, as shown in Figure . It can also be seen from Figure that there is little difference between the adsorption equilibrium capacity of the small sample mass and the large sample mass, which means that the sample amount does not affect the adsorption equilibrium capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In TGA, the solid sample is in a packed state on the crucible, and the gas has to diffuse from the gas cylinder to the TGA crucible. It is commonly acknowledged that the mass transfer limitations occurring inside the TGA will underestimate the kinetics. The mass transfer limitation can be improved by decreasing the mass of the solid amine sorbent, as shown in Figure . It can also be seen from Figure that there is little difference between the adsorption equilibrium capacity of the small sample mass and the large sample mass, which means that the sample amount does not affect the adsorption equilibrium capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Many solid amine sorbents have been tested using TGA to study the CO 2 adsorption kinetics. In TGA, the solid sample is in a packed state on the crucible, and the gas has to diffuse from the gas cylinder to the TGA crucible. It is commonly acknowledged that the mass and heat transfer limitations occurring inside the TGA will underestimate the kinetics. Some correction methods have to be used to reduce these measurement errors. , Different TGA apparatuses could also produce different kinetics. For example, Alonso et al studied the carbonation reaction in different TGA apparatuses and concluded that the design of the TGA oven can be a source of error, despite the same raw materials and reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion performance of pulverized coal is apparently influenced by the alteration from air to oxy-fuel combustion. ,, The unburnt carbon in fly ash from oxy-fuel combustion is usually higher than that from air combustion under the same O 2 content in experiments using an entrained flow reactor and drop tube furnace, while the case applying a fixed-bed reactor, including a thermogravimetric analyzer, is still ambiguous Figure depicts the comparison of ash yield between air and oxy-fuel conditions with O 2 content of 21%.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with air combustion, oxygen content is a flexible parameter to adapt the performance of oxy-fuel combustion in a furnace. Oxygen content indeed has a profound influence on combustion characteristics of coal particles under oxy-fuel condition. , Here, the impacts of oxygen content on ash yield and element transformation (Na, Ca, and Fe) were experimentally investigated as illustrated in Figure . The ash yield of WCW coal displays a decrease tendency with the rise of oxygen content in the O 2 /CO 2 atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation